Developing a Performance-Based Educational Leadership Competency Development Model with a Futures Studies Approach: A Systematic Meta-Synthesis of International Studies - Nazarizadeh Kermani, Maryam; Abbaspour, Abbas; Rahimian, Hamid; Taheri, Morteza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective: The present study aimed to develop a comprehensive model of performance-based educational leadership competencies using a futures studies approach through the systematic meta-synthesis of international studies published between 2015 and 2025. Methods and Materials: This study employed a qualitative meta-synthesis approach based on the interpretive framework of Noblit and Hare (1988) and the seven-step procedure of Sandelowski and Barroso. Scientific databases including Scopus, ERIC, Google Scholar, SID, Magiran, ScienceDirect, and Noormags were systematically searched using keywords related to educational leadership competencies, performance-based leadership, educational management, and competency development. Initially, 145 studies published between 2015 and 2025 were identified. After applying inclusion and exclusion criteria and conducting title, abstract, and full-text screening, 35 valid qualitative and mixed-method studies were selected for final analysis. Open coding, thematic synthesis, and axial categorization were utilized to extract conceptual categories and formulate the final competency model. Findings: The findings revealed that performance-based educational leadership competencies possess a multidimensional and interdisciplinary structure organized into three major levels: causal, executive, and contextual. At the causal level, macro-leadership, policy-oriented transformation, analytical leadership, and data-driven decision-making emerged as the primary drivers of educational transformation. At the executive level, transformational and innovative leadership, learner-oriented leadership, organizational learning, and human resource empowerment were identified as core dimensions of leadership performance. At the contextual level, higher education governance, organizational culture, decentralization, and supportive policy environments were recognized as structural foundations for leadership effectiveness. Conclusion: The results indicate that effective educational leadership in contemporary educational systems requires an integrated combination of transformational, analytical, learner-centered, and performance-based competencies.